2018
DOI: 10.3758/s13414-018-1540-9
|View full text |Cite
|
Sign up to set email alerts
|

Rapid recalibration to audiovisual asynchrony follows the physical—not the perceived—temporal order

Abstract: In natural scenes, audiovisual events deriving from the same source are synchronized at their origin. However, from the perspective of the observer, there are likely to be significant multisensory delays due to physical and neural latencies. Fortunately, our brain appears to compensate for the resulting latency differences by rapidly adapting to asynchronous audiovisual events by shifting the point of subjective synchrony (PSS) in the direction of the leading modality of the most recent event. Here we examined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 61 publications
2
30
3
Order By: Relevance
“…Serial dependencies in perceptual decisions can be driven by multiple factors, such as the previous stimuli (Bruns & Röder, 2015;Kayser & Kayser, 2018;Wozny & Shams, 2011b), the previous responses (Fritsche et al, 2017;Kiyonaga et al, 2017;Talluri et al, 2018), or a meta-cognitive assessment of previous behaviour (Benwell et al, 2019). Yet, previous work in young participants considered the ventriloquism aftereffect generally as a sensory-driven phenomenon Van der Burg et al, 2018). Confirming this view, we found that the sensory contribution to the aftereffect prevailed in the YA.…”
Section: Changes In Between-trial Multisensory Recalibration With Agesupporting
confidence: 87%
“…Serial dependencies in perceptual decisions can be driven by multiple factors, such as the previous stimuli (Bruns & Röder, 2015;Kayser & Kayser, 2018;Wozny & Shams, 2011b), the previous responses (Fritsche et al, 2017;Kiyonaga et al, 2017;Talluri et al, 2018), or a meta-cognitive assessment of previous behaviour (Benwell et al, 2019). Yet, previous work in young participants considered the ventriloquism aftereffect generally as a sensory-driven phenomenon Van der Burg et al, 2018). Confirming this view, we found that the sensory contribution to the aftereffect prevailed in the YA.…”
Section: Changes In Between-trial Multisensory Recalibration With Agesupporting
confidence: 87%
“…Indeed, the two prominent events during the AV trial are the exposure to a discrepant audiovisual stimulus and the corresponding response. Contrasting these two in their predictive power of the subsequent bias, we previously reported in favor of a sensory-rather than motorrelated origin of the ventriloquism aftereffect Park et al 2020;Van der Burg et al 2018). In the present dataset we found that the previous motor response contributes significantly, in addition to the multisensory discrepancy.…”
Section: The Neural Underpinnings Of the Spatial Ventriloquism Afterecontrasting
confidence: 72%
“…Previous work has suggested that adaptive recalibration, in particular on a trial-by-trial level, may not only be related to the previous sensory input but also to variables related to the reported experience, or previous motor response (Park et al 2020;Van der Burg et al 2018).…”
Section: The Neural Underpinnings Of the Spatial Ventriloquism Afterementioning
confidence: 99%
“…the previous multisensory discrepancy: Δ n-1 = V n-1 – A n-1 ) or the participant’s response in that trial (R n-1 ). Formal model comparison revealed that the model R n ~ 1 + A n + Δ n-1 provided a better account of the data than a response-based model R n ~ 1 + A n + R n-1 (relative BIC: 0, 393; BIC weights: 1, 0), supporting the notion that recalibration is linked more to the physical stimuli than the participants response (21).…”
Section: Resultsmentioning
confidence: 71%
“…However, we interact with our environment using sequences of actions dealing with different stimuli, and thus systematic sensory discrepancies as required for long-term effects are possibly seldom encountered. Hence, while the behavioral patterns of multisensory trial-by-trial recalibration are frequently studied (6,7,9,20,21) it remains unclear when and where during sensory processing their neural underpinnings emerge.…”
Section: Introductionmentioning
confidence: 99%